2008
DOI: 10.1111/j.1752-4571.2007.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Introgression and dispersal among spotted owl (Strix occidentalis) subspecies

Abstract: Population genetics plays an increasingly important role in the conservation and management of declining species, particularly for defining taxonomic units. Subspecies are recognized by several conservation organizations and countries and receive legal protection under the US Endangered Species Act (ESA). Two subspecies of spotted owls, northern (Strix occidentalis caurina) and Mexican (S. o. lucida) spotted owls, are ESA-listed as threatened, but the California (S. o. occidentalis) spotted owl is not listed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 93 publications
(145 reference statements)
1
39
0
Order By: Relevance
“…Hybridization between northern spotted owls and the other two subspecies of spotted owls (California spotted owls, S. o. occidentalis, and Mexican spotted owls, S. o. lucida) and/or genetic drift in small populations are more likely explanations for LD in northern spotted owls. Funk et al (2008) demonstrated hybridization between northern spotted owls and the other two subspecies in some study areas, suggesting hybridization could contribute to LD. Additionally, evidence for bottlenecks presented above suggests that effective population sizes are decreasing which should in turn result in increased genetic drift and LD.…”
Section: Recent Bottlenecks In Northern Spotted Owlsmentioning
confidence: 92%
See 2 more Smart Citations
“…Hybridization between northern spotted owls and the other two subspecies of spotted owls (California spotted owls, S. o. occidentalis, and Mexican spotted owls, S. o. lucida) and/or genetic drift in small populations are more likely explanations for LD in northern spotted owls. Funk et al (2008) demonstrated hybridization between northern spotted owls and the other two subspecies in some study areas, suggesting hybridization could contribute to LD. Additionally, evidence for bottlenecks presented above suggests that effective population sizes are decreasing which should in turn result in increased genetic drift and LD.…”
Section: Recent Bottlenecks In Northern Spotted Owlsmentioning
confidence: 92%
“…We did not observe consistent LD between the same pair of loci across populations, suggesting that LD was not due to physical linkage between loci. Moreover, previous analyses showed that there is little population structure within regions (Funk et al 2008), suggesting population structure is not the cause of LD. Hybridization between northern spotted owls and the other two subspecies of spotted owls (California spotted owls, S. o. occidentalis, and Mexican spotted owls, S. o. lucida) and/or genetic drift in small populations are more likely explanations for LD in northern spotted owls.…”
Section: Recent Bottlenecks In Northern Spotted Owlsmentioning
confidence: 94%
See 1 more Smart Citation
“…Further study is warranted to clarify the relationship of the population in California, which may also be disjunct to some degree with the eastern Oregon Cascades population, and is disjunct with other populations of the species. However, it appears that the population in the Sierra Nevada and Oregon Cascades is genetically distinct from other black-backed woodpecker populations, similar to the distinction between the northern spotted owl in the Pacific Northwest, a subspecies of Strix caurina that is listed as threatened [18,19], and the California subspecies, which is not listed. Therefore, in addition to the biodiversity for which it serves as an indicator or provides vital resources for reproduction, the black-back woodpecker is an important conservation concern in its own right in the Sierra Nevada and southern Cascades.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the Columbia River as a barrier appears to vary among species. In some, it corresponds with a genetic break (Monsen and Blouin, 2003), but in many it does not (Funk et al, 2008;Nielson et al, 2006;Recuero et al, 2006).…”
Section: Phylogeographic Breaksmentioning
confidence: 99%